Teachers’ perception of Technological Pedagogical Content Knowledge (TPACK) in Teaching at Senior High School in Pekanbaru - Syofianis Ismail; desi masari; Destina Kasriyati; Herdi Herdi; Refika Andriani (ELT-Lectura, 2023)
A framework called TPACK outlines the knowledge that instructors require in order to incorporate technology into the planning, carrying out, and assessing of learning. TPACK integrates diverse learning tactics, combining appropriate technology with thinking strategies for when, when, and how to employ technology knowledge, pedagogy, and material. Integration of technology in teaching is carried out by teachers at SMA Negeri Olahraga Riau. The aim of this study is to explain the teachers’ perception of TPACK in the teaching process at SMA Negeri Olahraga Riau. The method was descriptive quantitative, a survey research design with a sample of 30 teachers. The entire sampling method is employed. The major tool for gathering data was the questionnaire. The data were obtained by descriptive analysis, using the sum of the scores, the mean, and the standard deviation, and then were descriptively interpreted. The results indicate that most teachers believe their level to be quite high. Measured by averaging the seven TPACK indicators—technological knowledge, pedagogical knowledge, content knowledge, technological pedagogical knowledge, technological content knowledge, and technological pedagogical knowledge—into a single score. The results suggest that teachers have the skills necessary to incorporate the TPACK framework into their lesson plans.